2010
DOI: 10.1097/rhu.0b013e3181ffeb49
|View full text |Cite
|
Sign up to set email alerts
|

Benign Spontaneous Pneumoperitoneum in Systemic Sclerosis

Abstract: The gastrointestinal tract is commonly involved in patients with systemic sclerosis (SSc) (Am J Gastroenterol. 1972;58:30-44). Intestinal manifestations of SSc include impaired motility, malabsorption, bacterial overgrowth, jejunal and wide-mouthed colonic diverticuli, localized dilatation, pseudo-obstruction, and, less commonly, pneumatosis cystoides intestinalis (PCI) (Rheumatology. 2009;48:iii36-iii39; J Clin Gastroenterol. 2008;42:5-12). Benign spontaneous pneumoperitoneum is a rare complication of SSc and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Pneumoperitoneum in the absence of concerning clinical findings may not warrant invasive surgical procedures. Similar to two earlier case reports of benign spontaneous pneumoperitoneum in the presence of PI,12 15 our patients had a benign course with conservative management despite having pneumoperitoneum. Patient A's pneumoperitoneum resolved spontaneously whereas patient B's pneumoperitoneum persisted, though without symptoms or complications.…”
Section: Discussionsupporting
confidence: 90%
“…Pneumoperitoneum in the absence of concerning clinical findings may not warrant invasive surgical procedures. Similar to two earlier case reports of benign spontaneous pneumoperitoneum in the presence of PI,12 15 our patients had a benign course with conservative management despite having pneumoperitoneum. Patient A's pneumoperitoneum resolved spontaneously whereas patient B's pneumoperitoneum persisted, though without symptoms or complications.…”
Section: Discussionsupporting
confidence: 90%
“…4 Other theories suggest minute perforations in intestinal diverticula from ischemia. 5 Drugs, such as corticosteroids, have shown to deplete lymphatic tissue in the Peyer's patch cells of the intestine enabling gas entry into the intestinal wall. 1 A review of patients with systemic sclerosis and PI reported that 33% of them were on corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…4 Interestingly, benign spontaneous pneumoperitoneum may persist for years without development of peritonitis. 5 Since free air is absorbed from the peritoneal cavity, persistent pneumoperitoneum implies a continuous leak of air into the peritoneal cavity. As seen in our patient, those with CTD may not present with typical symptoms and may have a physical exam that is completely discordant with the severity of the imaging findings.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the most likely explanation for the absence of visible pneumatosis coli and/or intestinalis in the context of scleroderma-related pneumoperitoneum may be that the intramural air is too subtle to detect on conventional imaging. Another less likely explanation is that the patient may have been imaged on each occasion at a time when the pneumatosis had spontaneously resolved but the pneumoperitoneum still persisted [6]. An alternative explanation for the pneumoperitoneum may be recurrent microperforations of the intestinal wall, which allowed gas leakage from the bowel directly into the peritoneal cavity [3,5].…”
Section: Discussionmentioning
confidence: 99%